Biochemical Composition and Nutritional Value of Fresh Tuber of Water Yam (Dioscorea alata L.) Local Accessions from East Java, Indonesia - Fauziah, Fauziah; Mas'udah, Shofiyatul; Hapsari, Lia; Nurfadilah, Siti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Water yam (Dioscorea alata L.) is an important tuber crop containing essential nutrition as an alternative food source. This study aimed to analyze the biochemical composition and nutritional value of fresh tuber of fifteen local accessions of water yam from East Java and followed by the accession selection for the recommendation of accession with the best nutritional value. Results showed that the nutritional value of proximates including moisture, carbohydrate and fiber were significantly different; except in protein, fat, and ash, with the range of moisture (65.47-82.46%), carbohydrate (17.10-29.37%), protein (1.29- 3.00%), fat (0.00-0.29%), fiber (6.70-11.62%) and ash (0.85-1.44%). The ranges of mineral contents (mg/100g) were K (224.54-483.21), Ca (15.63-61.97), Mg (16.75-43.06), Fe (1.40-13.40), Zn (0.43-2.83) and P (329.37-699.91); Na mostly not detected. The anti-nutritions contents (mg/100g) comprised tannin (63.36-167.68) and oxalic acid (12.73-44.92). Analysis through HCA showed three clusters with a range of similarity from 67% to 96%; through PCA scatter biplot clearly illustrated the variation and correlation pattern among local accessions. Six promising accessions are recommended for further breeding and development i.e. Uwi Perti/30, Uwi Bangkulit/36, Uwi Bangkulit/42, Uwi Bangkulit/43, Uwi Biru/58 and Uwi Legi/66, based on their highest carbohydrates and protein content, and the lowest fat content.